Comparative analysis of the corrosion resistance data of aluminium alloy 4032 and 4004, magnesium titanium alloy and aluminium vanadium alloy in dilute H2SO4, NaCl and acid chloride solutions - Olaolorun Ayomide; Ikhionose Igenuma Daniel; Ayobami Sonde David; Eberechukwu Emmanuel Achonwa; Afolami Fanifosi; Tobechukwu Okoroji; Morounfoluwa John; Okeniyi Joshua; Loto Roland Tolulope (E3S Web of Conferences)
Comparative study of the corrosion resistance of Al 4032, Al 4004, Mg-Ti and Al-V alloy were performed in H2SO4 solution, NaCl solution and H2SO4/NaCl solution for 480 h. Mg-Ti exhibited the highest corrosion rate values in H2SO4 solution, culminating at values between 0.242 mm/y and 6.081 mm/y compared to Al 4004 and Al 4032 which exhibited the lowest values. Corrosion rate of Al-V were generally stable but exhibited a parabolic behavior beyond 0.025 M H2SO4 concentration. In NaCl, Mg-Ti alloy exhibited the highest corrosion rate values culminating at values from 0.180 mm/y to 0.794 mm/y. Al 4004 and Al-V alloys exhibited the lowest corrosion rate values. The corrosion rate of Al 4032 was generally stable throughout the exposure hours. Admixture of H2SO4 and NaCl did not significantly influence the corrosion resistance of the alloys. ANOVA statistical data for Al 4032, Al 4004 and Al-V alloys in NaCl solution are statistically irrelevant with respect to corrosion resistance of the alloys compared to the value for Mg-Ti where electrolyte concentration is statistically relevant with statistical relevance factor of 96.94%. Electrolyte concentration is the only statistically relevant variation influencing the corrosion resistance for the alloys in H2SO4 with values of 98.44%, 97.66%, 94.96% and 98.38%. This was also observed in H2SO4/NaCl solution with corresponding values of 90.02%, 94.35%, 91.71% and 86.7%. The highest mean values for Al 4032, Mg-Ti, Al 4004 and Al-V alloys occurred at 0.05 M, 0.0125 M and 0.00625 M H2SO4 solutions. Mg-Ti exhibits the highest mean corrosion rate values of 5.93 mm/y while Al-V exhibits the lowest values -0.10 mm/y. The SD values were generally low. The mean corrosion rate values for Al 4032, Al 4004 and Al-V alloys in NaCl are significantly below 0 compared to Mg-Ti whose values are greater than 0 but relatively low.